Effects on ecosystems due to the presence of heavy metals in small-scale mining activity in Puno - NOVOA VILLA, HECTOR HUMBERTO (2022)
Small-scale mining is growing with a greater number of operators in different parts of the world, the Puno-Peru region does not escape this reality; collaterally, the negative impacts on ecosystems are increasing, the objective of the study is to determine the presence of heavy metals as a result of artisanal mining activity in the provinces of Sandia, Carabaya and San Antonio de Putina. Seven specific water samples were taken close to the operations of the three provinces, evaluated in a plasma spectrometry equipment (ICP) and 10 samples in the town of Rinconada analyzed in a Milestone DM 80 equipment exclusively for mercury analysis; in the first block, aluminum (Al) was present in ranges from 7.79 to 66.2 mg/L; chromium (Cr) with a sample with 0.12 mg/L; iron (Fe) with ranges from 36.1 to 280 mg/L; mercury (Hg) with ranges from 0.0158 to 0.1301 mg/L; manganese (Mn) varying from 0.4004 to 6.5092 mg/L and nickel (Ni) with values between 0.2278 and 1.2148 mg/L, six samples except one present metals that exceed the environmental quality standards for irrigation and animal drink. In Rinconada, where more than 400 contractors operate, living with around 30,000 people; yielded results that vary between 0.0013 and 0.0188 mg/l for mercury, higher than those allowed according to national and international regulations; the results show the negative effects for the ecosystems and the health of the people of the environments.